Geographic and climatic factors related to a body-size cline in Dichroplus pratensis Bruner, 1900 (Acrididae, Melanoplinae) - Bidau, Claudio Juan (2008)
We studied geographic body size variation in males and females of 25 populations of the South American melanopline grasshopper Dichroplus pratensis Bruner, 1900, along more than 22 degrees of latitude (S) and between 0 and almost 2500 m of altitude. Using mean body length of each sex and factors obtained from PCA analyses of six morphometric linear characters, it was shown that D. pratensis follows the converse to Bergmann’s rule, becoming smaller at higher latitudes and altitudes. Variability of body size increased with latitude and altitude in males and females. Body size trends were statistically significantly correlated with ambient temperature (annual mean, minimum and maximum), precipitation (annual, minimum and maximum), and two estimators of seasonality, the difference between the maximum and minimum temperatures, and the difference between maximum and minimum precipitation for each locality; both nonparametric correlations were positive. Body size was also positively and significantly correlated with Actual Evapotranspiration (AET), a measure of primary productivity, and with Potential Evapotranspiration (PET), a measure of ambient energy, but not with water balance (WB). Some allometric relationships also showed geographic variation. We suggest that the observed decrease in size with latitude and the increase in morphological variability are joint consequences of the shortening of the growing season towards the south, the increasing seasonality and climatic unpredictability, lower primary productivity (as represented by AET), and that the species exhibits protandry, which contributes to smaller and more variable size in males, and smaller but more constant body size in females, in the south.